1994
DOI: 10.1161/01.hyp.23.4.513
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium and blood pressure in experimental models of hypertension. A review.

Abstract: More than 80 studies have reported lowered blood pressure after dietary calcium enrichment in experimental models of hypertension. The evidence presented here suggests that dietary calcium may act concurrently through a number of physiological mechanisms to influence blood pressure. The importance of any given mechanism may vary depending on the experimental model under consideration. Supplemental dietary calcium is associated with reduced membrane permeability, increased Ca(2+)-ATPase and Na,K-ATPase, and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(70 citation statements)
references
References 230 publications
5
64
1
Order By: Relevance
“…19 Phosphorus is also intimately involved in calcium regulation 20 ; calcium has a membrane stabilizing effect 40 with a key role in vascular smooth muscle function. 41 Sodium loading raises intracellular calcium levels, 42 increasing contractility, whereas calcium loading decreases these levels, presumably via calcium-regulating hormones. 43 Magnesium also plays an important role in transmembrane calcium transport and the regulation of vascular tone and endothelial function.…”
Section: Elliott Et Al Dietary Phosphorus and Blood Pressurementioning
confidence: 99%
“…19 Phosphorus is also intimately involved in calcium regulation 20 ; calcium has a membrane stabilizing effect 40 with a key role in vascular smooth muscle function. 41 Sodium loading raises intracellular calcium levels, 42 increasing contractility, whereas calcium loading decreases these levels, presumably via calcium-regulating hormones. 43 Magnesium also plays an important role in transmembrane calcium transport and the regulation of vascular tone and endothelial function.…”
Section: Elliott Et Al Dietary Phosphorus and Blood Pressurementioning
confidence: 99%
“…The involvement of Ca 2ϩ in coronary and vascular smooth muscle (VSM) reactivity has a bearing on vessel tone and blood pressure control. High Ca 2ϩ intake has been shown to lower blood pressure in animal models of hypertension (31,32,40,50), and diets high in fruits and vegetables, supplemented with predominantly low-fat milk, significantly reduced blood pressure compared with fruit-and vegetable-only diets (1,3,4,57). Current evidence suggests that adequate Ca 2ϩ intake (1,000 -1,500 mg/day) is critical to optimal blood pressure regulation, and randomized controlled trials have revealed significant reductions in hypertension risk and blood pressure levels in humans (48,49).…”
mentioning
confidence: 99%
“…Meta-analyses of randomized trials have reported a 22.6 mmHg reduction in SBP with calcium supplementation (3) and a 24.8 mmHg reduction in SBP with milk tripeptides (4) in populations with relatively low calcium intake. Calcium deficiency can increase the parathyroid hormone level, which in turn increases blood pressure (28). Other mechanisms that potentially explain our findings include direct effects on vascular smooth muscle, calcium regulation, and calciumsensitive hormones; interactions between calcium and sodium potassium; and an increased appetite for sodium when calcium intake is low (28).…”
Section: Discussionmentioning
confidence: 76%
“…Calcium deficiency can increase the parathyroid hormone level, which in turn increases blood pressure (28). Other mechanisms that potentially explain our findings include direct effects on vascular smooth muscle, calcium regulation, and calciumsensitive hormones; interactions between calcium and sodium potassium; and an increased appetite for sodium when calcium intake is low (28). In addition to calciumrelated mechanisms, milk-derived tripeptides are potent inhibitors of angiotensin-converting enzymes (4).…”
Section: Discussionmentioning
confidence: 99%